The traditional economy of Yakutia and AIC “Sever”: organizational and managerial decisions of the second half of the 1980s — 1991 - Yana M. Sannikova (Arctic and North, 2018)
On the basis of archival documents, entered into scientific circulation, the author considers the local experience of organizational and management activities in relation to the farms of the North of Yakutia within a specially created agro-industrial complex (AIC). In the considered period of the AIC “Sever” ac-tivities, in 1989-1991, organizational processes of unbundling of state farms and the beginning of reorgani-zation of management were decisive. At the end of 1990s, for the first time, decisions on transition to market relations were officially declared by the AIC. At the same time, the real social and economic situation of farms had already begun to show the deterioration, incl. a decrease in the quantitative indicator — reduction in the number of farms in the studied areas. As it is in the documents, the state of home reindeer husbandry, the leading economic sector in the North, was of a particular concern.